Penggunaan Aplikasi Emaze Sebagai Media Pembelajaran Seni Budaya di SMA Pembangunan Laboratorium UNP - Alif Multahul Risna; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2022)
This study aims to describe the use of the Emaze Application as a Learning Medium for Cultural Arts (Dance) at the UNP Laboratory Development High School. This type of research is qualitative research using applied descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data type uses primary data and secondary data. Data collection techniques are carried out by means of observation, interviews and documentation. The steps of analyzing data are data classification, data clarification, analyzing data, describing data and inferring data. The results showed that the use of the Emaze application as a medium for learning cultural arts (dance) in class X of the UNP Laboratory Development High School is very helpful for educators in delivering material to students more structured and interesting. Students' learning motivation increases with the 3D view and other advantages of the Emaze application. This can be seen from the results of student practice exams that are very satisfactory and achieve learning objectives in accordance with the syllabus and rpp. Teachers really appreciate the use of the Emaze application and are excited to learn to use the Emaze application in order to be able to use it when teaching and students like and are even interested in using the Emaze application again during learning using the discussion method. However, not all students expressed this, there are also those who are opposed to the above statement but the number who support the use of the Emaze application is very far from those who do not support it.